Accelerating youth-led digital entrepreneurship in agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Young people have the potential to generate innovations that will transform the productivity and resilience of agriculture in Africa, the Caribbean and the Pacific (ACP). For over five years, CTA has been promoting and supporting digital entrepreneurship among tech-savvy youth to improve their livelihoods, their communities, and contribute to the ACP’s agricultrual transformation. CTA’s approach to facilitating digital entrepreneurship among young people in ACP regions, includes the identification of promising young entrepreneurs; peer-to-peer learning; networking and business-to-business (B2B) matchmaking; mentorship and capacity development; and piloting business models for proof of concept and impact assessment.